Mid-to Late Holocene paleoclimatic changes and paleoenvironmental shifts inferred from pollen and diatom assemblages at Lake Hamra, Wadi El Natrun (Western Nile Delta, North Western Desert, Egypt). (20th March 2020) - Zaky, Amr S.; Kashima, Kaoru; Frontalini, Fabrizio; Ibrahim, Mohamed I.A.; Khalifa, Moataz M.; Fukumoto, Yu; Gad, Dina; Behling, Hermann
Abstract: Four palynological and three diatom zones of Mid-to Late Holocene are identified along a 370-cm-long radiocarbon dated sediment core collected in Lake Hamra at Wadi El Natrun (Western Nile Delta, Egypt). The Mid- Late Holocene between the Predynastic to Old Kingdom was terrestrial wetland habitat with high seasonal rainfall and/or Nile flood as revealed by the dominance of Cyperaceae pollen. Therefore, people gathered in and around the Nile Valley and the agricultural activities increased. During the early stage of Late Holocene coincident with the Old Kingdom to Middle Kingdom, the paleoclimate became more arid with low seasonal precipitation and/or Nile flood as reflected by the increasing abundance of Poaceae pollen and the absence of diatoms in addition to low values of TOC, TN, TS, C/S and high values of C/N. These drought conditions possibly played a role in the Old Kingdom collapsing. The late stage of the Late Holocene showed terrestrial wetland habitat with brackish conditions coupled with aquatic contribution under oxic conditions as inferred by the dominance of Typha sp. and Amaranthaceae pollens as well as the diatom assemblages. The relatively high values of TOC, C/N, C/S coupled with low values of TS and TN reveal terrestrial origin of organic matter. The Late Holocene-recent has turned into a terrestrial wetland habitat with more brackish conditions and increasing in the seasonal rainfall as supported by the marked increasing of Cyperaceae pollen. The overall increase of the Diatom Inferred Salinity (DIS) as well as the marked increasing of C/S, TN and decreasing of TOC, C/N and TS values towards the recent point to higher saline brackish wetland paleoenvironment and a terrestrial origin of the organic matter with more aquatic contribution under oxic conditions.